Benefits of E-Commerce in Marketing Creative Industrial Products - Jefry Romdonny (Budapest International Research and Critics University, 2019)
This study aims to determine the benefits of e-commerce for creative economic actors, especially to market their products. The research method uses is qualitative with an analytical and explorative descriptive approach. From the research conducted, the results shows that the use of e-commerce has a positive impact on both producers and consumers. While the benefits for producers are that promotional costs can be reduced so that the selling price can be more competitive. However, the limited ability of human resources to utilize information technology and capital is a major obstacle for micro-entrepreneurs. The role of the regional government, especially the related institutions, is expected to be able to provide guidance and solutions for the development of the creative economy in the region.